Telephone-based group mental health support for older adults in central Canada: pilot acceptability and effectiveness findings of The CONNECT Program - Reynolds, Kristin Audrey Alison; Kudar, Kira; Joshi, Jarod; Christianson, Inga; Davidson, Dylan; Gopinath, Georgia; Koven, Lesley; Mackenzie, Corey; Miller, Stacey; Newall, Nancy (Frontiers in Public Health, 2025)
BackgroundThough experiences of anxiety, depression, loneliness, and social isolation are prevalent among older adults, treatment access is limited. In central Canada, based on participatory program development methods, our team of researchers, clinical psychologists, and community experts have developed and piloted a novel 6-session telephone-based group intervention called The CONNECT Program, based on the principles of Acceptance and Commitment Therapy (ACT), self-compassion, and psychosocial theories of successful aging.MethodsWe offered The CONNECT Program by telephone from September 2020 to February 2022, completing 7 intervention groups with N = 34 participants. We collected quantitative data at baseline and quantitative and qualitative data post-intervention by telephone.FindingsOverall, our program was deemed to be feasible and acceptable by participants. Pre- to post-CONNECT, we found significant improvements in depression (d = 2.4), emotional support (d = 5.2), mental health literacy (d = 3.2), and psychological flexibility (d = 7.0), indicating large treatment effects. Through conventional content analysis of post-CONNECT individual interviews we developed three main themes: Accessibility (sub-themes: join from the comfort and anonymity of the telephone lines; reduction of age-related barriers), Connectedness (sub-themes: connection to group facilitators; group members; and new information), and Perceived Program Benefits (sub-themes: behavioral changes; emotional and cognitive changes; enhanced mindful awareness).DiscussionThe CONNECT Program is a novel, accessible, and acceptable intervention that demonstrates promise in improving key social and mental health indicators. The findings from this pilot study will inform a future trial comparing The CONNECT Program with standard community programs typically offered to older adults in these provinces. This trial will also evaluate two delivery modes (telephone and videoconferencing) to compare their relative impact and feasibility.